The Impact of Real Effective Exchange Rate on Economic Growth: Algeria Case Study - Zirar, Sumaya; Moussaoui, Mohammed (Jordan Journal of Economic Sciences, 2015)
The purpose of this study is to determine the effect of real effective exchange rate on the economic growth in Algeria from (1980-2013), by using the cointegration test and the Fully-Modified OLS method, the study found a long run relationship between economic growth and variables: money supply, labor productivity, government expenditure, and real effective exchange rate, the estimation shows also that the real effective exchange rate has a negative effect on the economic growth